Hubungan Antara Reliability dan Responsiveness dengan Loyalitas Pasien di Ruang Rawat Inap - Liza Wati (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine the relationship of reliability and responsiveness of nursing with patient loyalty in the inpatient room of Tanjungpinang City Hospital. Research design with a correlational study approach. The results showed that more than half of the respondents came from the early adult age group of 38 people (57.6%), female sex (51.5%), highly educated (50%), and working (77.3%). Based on the distance of the respondent's residence, it is found that more than half of the respondents live far from the hospital (57.6%), in general respondents use insurance (83.3%). Based on treatment experience, it is known that more than half of patients have never been treated at Tanjungpinang City Hospital (57.6%). The results showed the perception of reliability (p = 0.008), and perception of responsiveness (p = 0.002). Conclusion, there is a significant correlation with patient loyalty, strength of relationship and positive direction. The most dominant variable is responsiveness. Keywords: Patient Loyalty, Nursing Services, Reliability, Responsiveness